ADEKWATNOŚĆ KSZTAŁCENIA JĘZYKOWEGO W SIŁACH ZBROJNYCH RZECZYPOSPOLITEJ POLSKIEJ DO REALNYCH POTRZEB UCZĄCYCH SIĘ - Werona Król-Gierat , Werona (Neofilolog, 2020)
This paper presents the organization of language education in the Polish Armed Forces, which today focuses mostly on English instruction and is based on STANAG 6001. It highlights the importance of two key institutions, namely the Military Education Department and The Polish Armed Forces School of Languages. The final section deals with the military thematic units suggested in the language curriculum designed for soldiers and evaluates the presence of these themes in certification papers issued by the Central Examination Board for Foreign Languages of the Ministry of National Defence.